Avaliação da indexação em bibliotecas universitárias: uma aplicação em catálogos online - Inácio, Mariana de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The evaluation of the indexing is essential, in general, to the library or another information service, as it can be regardes as a tool that helps the librarians achieve the organizational effectiveness and efficiency, optimizing products and services. Considering the urgency of the enlargement of investigations around the evaluation of indexing, and the deficit of literature and manuals that assist this activity, it is proposed to investigate the applicability of the method of evaluation for indexing in Online Catalogues for University Libraries. Thus, we investigate the applicability of different methods of evaluation of indexing, specifically the intrinsic qualitative assessment of Online Catalogues in the context of university libraries. The specific objectives are; realizing a study of the theoretical and methodological evaluation of indexing assessment in the context of university libraries, and investigating the intrinsic qualitative evaluation method in online catalogues of university libraries, seeking to contribute to the elaboration of a Manual Assessment indexing, to ensure both the continuous applicability of studies on this topic and the improvement of information retrieval in Online Catalogues in academic libraries. For this goal, as methodological procedures in the first instance, it is carried out a survey on theoretical and methodological evaluation of indexing, and in a second moment, the applicability of a qualitative intrinsic assessment of their elements inherent to quality of indexing, associated to complementary techniques on participant observation and Interactive Verbal Protocol . In short, it is confirmed the deficit in the literature on evaluation index and the inexistence of manuals of evaluation on... (Complete abstract click electronic access below)

A avaliação da indexação é imprescindível, de um modo geral, para a biblioteca ou para outro serviço de informação, visto que pode ser considerada uma ferramenta que auxilia o bibliotecário a alcançar eficácia e eficiência organizacionais e otimizando produtos e serviços. Considerando a urgência da ampliação de investigações entorno da Avaliação de indexação, bem como o déficit de literatura e de manuais que auxiliem a atividade, propõe-se a investigação da aplicabilidade do método de avaliação de indexação em catálogos online para Bibliotecas Universitárias. Desse modo, investiga-se a aplicabilidade de diferentes métodos da Avaliação da indexação, especificamente Avaliação intrínseca qualitativa em catálogos online em contexto de bibliotecas universitárias. Tendo como objetivos específicos, realizar estudo teórico e metodológico sobre a Avaliação de indexação com enfoque no contexto de bibliotecas universitárias e investigar o método Avaliação intrínseca qualitativa em catálogos online de bibliotecas universitárias. Buscando contribuir com subsídios para a elaboração de um manual de Avaliação de indexação, que assegurem tanto a aplicabilidade contínua de estudos nesta temática quanto o aprimoramento da recuperação da informação por catálogos online em bibliotecas universitárias. Para tanto, como procedimentos metodológicos, em primeira instância realiza-se um levantamento teórico e metodológico sobre avaliação de indexação e, em um segundo momento, a aplicabilidade da Avaliação intrínseca qualitativa e de seus elementos inerentes à qualidade da indexação, associados a técnicas complementares a Observação participante e ao Protocolo Verbal Interativo. Em suma, confirma-se o déficit de literatura sobre a Avaliação na...
Keywords: Biblioteconomia - Indexação; Indexação - Avaliação; Indexação - Recuperação da informação